Stabilization Of Local Expansive Sub-Grade Soil Using Marble Waste Powder With Lime - Amdegebreal, Girmaw (My University, 2016)
Expansive soils are the most problematic soils due to their property of swelling and expansion with the influence of variable moisture, a number of civil engineering structures were destroyed. A billions of US doralls spent worldwide each year to mitigate the problem. The presence of expansive subgrade soil results pavement distress and damage. Removing the expansive soil and replacing with the competent material is applied to mitigate the problem which is very expensive and time consuming for long hauling distance and thick layer expansive soil. This study presented stabilization of local expansive subgrade soil using marble waste powder with lime. The marble waste powder was collected in Addis Ababa from Ethio-marble processing enterprise Gulele branch and the lime was collected at Gast Solar Mechanics in Addis Ababa. Free swell index test, Atterberg limit test, Proctor test, unconfined compressive test, California Bearing Ratio Tests, swelling potential and swelling pressure test were used to evaluate properties of treated and untreated soils. The expansive subgrade soil was treated using 5%, 10%, 15%, 20%, and 25% marble waste powder with fixed 3% lime respective combinations by weight of the soil. The optimum percent combination for this study was 10% marble waste powder with 3%lime based on soaked CBR swell, soaked CBR, swelling pressure and swelling potential test result values. Optimum proportion of stabilizers improve CBR Value from 0.65% to 4.19%, reduce swelling pressure from 1000kpa to 440kpa, increases MDD from 1.21 to 1.29, and reduce PI from 78% to 48.4%.